Pelatihan Kultivasi Mikroalga Skala Open Raceway Ponds - Welmar Olfan Basten Barat; Winfrontstein Naibaho (CERED Indonesia Publishing, 2022)
The high cultivation activity in Indonesia presents its own challenges, namely the high production costs which result in the burden of using feed (pellets). Therefore it is necessary to make a new breakthrough to overcome this problem, namely by utilizing microalgae as natural food for fish, especially in the seed phase. Besides being able to reduce production costs, it is also able to produce superior seeds. Microalgae are aquatic plants that have a very important role in waters because they are at the bottom of the food chain system (primary producers). Microalgae are a type of aquatic plant that can grow in a relatively short time. During its life, microalgae go through 5 phases namely the lag phase, logarithmic phase, decreased growth phase, stationary phase and death phase. Microalgae biomass contains important materials that are very useful, such as proteins, carbohydrates, fats and nucleic acids. The microalgae content can be used as a basis for making quality natural food. The aim of this training is to improve community skills in conducting mass-scale microalgae cultivation using the Open raceway ponds method independently. The results of the training showed that the level of understanding and technical ability of the participants was good based on the results of the material exam and the results of the practical tests measuring air quality and measuring the density of microalgae cells.